Dynamic simulation tool for a performance evaluation and sensitivity study of a parabolic trough collector system with concrete thermal energy storage - Sattler, Johannes Christoph; Caminos, Ricardo Alexander Chico; Atti, Vikrama; Ürlings, Nicolas; Dutta, Siddharth; Ruiz, Victor; Kalogirou, Soteris A.; Ktistis, Panayiotis K.; Agathokleous, Rafaela; Alexopoulos, Spiros; Boura, Cristiano Teixeira; Herrmann, Ulf (My University, 2020)
Plant developers of parabolic trough collector (PTC) systems for industrial steam generation face various challenges. Some of the main challenges are availability of land, buildings in the vicinity of the plant that cast shadows on the collectors as well as land restrictions. The typical north-south collector axis alignment in many cases may not be possible due to limits of available ground. These were challenges that were faced in the planning phase for installing a PTC plant on the premises of the KEAN Soft Drinks Ltd factory in Limassol, Cyprus. As these issues cannot be avoided they must be accounted for by the plant developer, especially when a performance guarantee is given. This work presents, amongst other things, factors that should be analysed in order to predict the energy yield in the planning phase as best as possible by using a simulation model. In the sensitivity study presented in this paper, several effects on the energy yield were investigated theoretically. These effects include: Tracking inaccuracy, non-parallel collector row axis orientations as well as north-south vs. east-west collector alignment. A dynamic simulation model developed by the Solar-Institut Jülich (SIJ) [1] was further developed and used for the analysis. The simulation model features a deviation between the measured and simulated oil temperature at the collector outlet of only 1.5 K (rms). The findings are presented in this paper and give an insight into the effectiveness of mid-sized PTC systems for the industry sector.
Keywords: Fresnel Reflectors; Solar Power Plants; Solar Thermal Energy